Friedrich Engels, South Slavdom, Democratic Pan-Slavism or Contrarevolution - Šutović, Milojica M. (Sociološki pregled, 2019)
The emergence, disintegration and disappearance of Yugoslavia, the structural and historical consequences, make Engels’ combination of theoretical-analytical perspicacity and publicist form in the critique of Pan-Slavism, democracy and the counterrevolution of the South Slavs (especially Austrian) during the European “Spring” (1948) current again. Their millennial tradition of denationalization, subjugation and mutual hatred and conflict is understood as an obstacle to the creation of a free and independent common state, which is expressed as a sentimental phrase and fantasy of people’s betrayal, threatened even by destruction in one world war. But this did not prevent Friedrich Engels, examining the historical material, describing the facts of his time and understanding the history of society as history of class struggle, to propose the necessary, simple and final solution of the Eastern issue, the creation of a free independent Christian Slavic state on the ruins of Islamic (Ottoman) Empire, with the special role of England, which must not allow the entry of Russia into the Balkans and the conquest of Constantinople. This was an anticipation of Yugoslavia, exactly 65 years before its foundation with the final destruction of the Turkish Empire. Engels did not predict the collapse of the Austro-Hungarian Empire. This does not diminish the significance of his analyses. The disintegration of Yugoslavia, in spite of the Western bias and anti-Russian orientation, gives them even more momentum, relevance and lucidity. The Western powers, Russia and Turkey, as in the time of Engels, continue to fight for dominance in the Balkans. The Balkan peoples, set against each other, live in some kind of confusion of undefined sovereignty and protectorate.